Development of Video-Based Online Course “SkillUp!ECT” to Enhance 4C Skills in Preschool Teachers - Suti Mega Nur Azizah; Zulfa Ulil Karomah; Laksamana Adipura; Sinta Yunita Sariningtyas Asri; Evania Yafie (Jurnal Media dan Teknologi Pendidikan, 2026)
The rapid advancement of technology and digitalization in the Society 5.0 era requires teachers to possess 21st-century competencies, particularly the 4C skills (critical thinking, communication, collaboration, and creativity). However, limited access to professional development opportunities has resulted in some early childhood education teachers not optimally mastering these skills. This study aims to develop and evaluate the feasibility of the SkillUp!ECT platform as a video-based online course to enhance teachers’ 4C skills. This study employed a research and development (R&D) approach using the ADDIE model, which includes analysis, design, development, implementation, and evaluation stages. The subjects of this study consisted of content experts, media experts, and early childhood education teachers as users. Data were collected through validation questionnaires and practicality tests using Likert-scale instruments and were analyzed using descriptive quantitative techniques. The results indicate that the developed platform demonstrates a high level of validity and practicality and is categorized as highly feasible. These findings suggest that SkillUp!ECT is effective as a professional development medium for teachers. The implication of this study is that the platform can serve as a flexible and innovative solution to support the continuous improvement of teachers’ 4C competencies.